The EFFECTIVENESS OF UTERINE MULTI- MICRONUTRIENT SUPPLEMENTATION COMPARED WITH BLOOD- BOOSTING TABLETS TO THE LEVEL OF MMUNOG LOBULINE G IN PREGNANT WOMEN TRIMESTER II ANEMIA - Novianto Novianto; Sri Sumarmi; Widati Fatmaningrum (Jurnal Ilmu Kesehatan, 2020)
The need for nutrients intake during pregnancy is very important to determine the quality of a child in the future. Several micronutrients take a key role for stimulating the immune system . Zinc is the most important one. This study aims to evaluate the effect of multi micronutrient (MMN) on immunoglobulin G levels of the anemic pregnant women in Second trimester, compared to iron folic acid (IFA). A single blind randomized controlled trial was conducted in Surabaya City. The samples size of 30 pregnant women were randomly allocated into two groups or 15 pregnant women in each group. Control group received iron folic acid , and the treatment group received multi micronutrient UNIMMAP formula. Either IFA or MMN was consumed daily for one month. Statistics analysis was done using Chi square test on data (age, education, income), paired t test , independent t test and the data are not normally distributed then use Mann Whitney. The results showed no significant difference in immunoglobulin G level between the two groups. It can be concluded that the administration of multiple micronutrients (MMN) cannot increase immunoglobulin G in pregnant women with anemia, this is probably due to consumption of macro nutrients that are poor compared to daily needs during pregnancy.